Socioeconomic dynamics of gender disparity in childhood immunization in India, 1992-2006. - Ranjan Kumar Prusty (Public Library of Science (PLoS), 2014)
Background Recent evidence indicated that gender disparity in child health is minimal and narrowed over time in India. However, considering the geographical and socio-cultural diversity in India, the gender gap may persist across disaggregated socioeconomic context which may be masked by average level. This study examines the dynamics of gender disparity in childhood immunization across regions, residence, wealth, caste and religion in India during 1992-2006. Method We used multi-waves of the cross-sectional data of National Family Health Survey conducted in India between 1992-93 and 2005-06. Gender disparity ratio was used to measure the gender gap in childhood immunization across the selected socioeconomic characteristics. Multinomial regression analysis was used to examine the gender gap after accounting for other covariates. Result Results indicate that, at aggregate level, gender disparity in full immunization is minimal and has stagnated during the study period. However, gender disparity--disfavouring female children--becomes apparent across the regions, poor households, and religion--particularly among Muslims. Adjusted gender disparity ratio indicates that, full immunization is lower among female than male children of the western region, poor household and among Muslims. Between 1992-93 and 2005-06, the disparity in full immunization had narrowed in the northern region whereas it had, astonishingly, increased in some of the western and southern states of the country. Conclusion Our findings emphasize the need to integrate gender issues in the ongoing immunization programme in India, with particular attention to urban areas, developed states, and to the Muslim community.